PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN PENGALAMAN DIKLAT TERHADAP KOMPETENSI PROFESIONAL GURU - Yurnaningsih, Antiek (Economic Education Analysis Journal, 2012)
The purpose of  this research is to determine the level of  influence between headmaster leader-ship and trainning experience on proffesional competance in senior high school economics/accountancy teachers Kudus ditrict simultaneously and partially. Populations that used in this research is all of  the economics/accountancy teachers in senior high school Kudus dis-trict (51 people). Methods of  data collection are documentation, questionnaire, and interview. Methods of  data analysis is descriptive and hypothesis testing using multiple linear regression analysis. Headmaster leadership and trainning experience simultaneously affect the proffe-sional competance (40,7%), headmaster leadership partially affect the proffesional competance (17,22%) and partially affected the trainning experience of  teacher’s proffesional competance (32,26%).